Evolution of Commercial Facilities in New Urban Areas of Hanoi: Potential of Sustainable Neighborhood-level Third Place Making - Tran, Minh Tung; Chu, Ngoc Huyen; Phan, Tien Hau (International Journal of Sustainable Construction Engineering and Technology, 2021)
Shopping contributes largely to how people feel part of and enjoy KDTMs (Khu Do Thi Moi - new urban areas) - the carefully planned new sites, well provided with infrastructure, and very attractive of Hanoi in the market economy. Among the three facilities that are rated as most important by KDTMâ€™s residents - education, health care, and shopping, the third is considered a pure civil space. This space clearly reflects the changes of politico-economic context and decision-making actors. Participation of the private sector in the newly formed market economy after a long period under State-run subvention and the consumerism entailed various ways to develop neighborhood-level commercial facilities. This paper aims to analyze and discuss on: firstly, the neighborhood-level commercial facilities have â€˜promptlyâ€™ updated the changes in Vietnam’s political-economic; secondly, the classify of KDTMs has resulted in a corresponding differentiation of commercial facilities according to the will of the project owners and the target consumer-resident; finally, facing the global â€˜deathâ€™ of shopping malls, the KDTMs malls are trying to find themselves a new â€˜vitalityâ€™: they are being â€˜publicizedâ€™ to (re)create the third places in KDTM, that encourage social interaction in the limited spaces - intersperse public and private practices.